CURRENT VIEW ON MORPHOLOGY OF ACUTE REJECTION IN LIVER TRANSPLANTATION - L.V. Shkalova; I.M. Iljinsky; O.M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
We present a scientific literature data analysis of morphological features and severity criteria of the liver allograft acute rejection during last 20 years. Modern conception was given about the role of immunological mechanisms in the de- velopment of liver graft acute rejection. We describe roles of different cell types in the destructive immune response during liver allograft acute rejection. Advantages and disadvantages of Banff-classifications 1995, 1997 are discussed as well as the necessity of grading the acute rejection as early and late. We propose clinico-morphological correlations in liver allograft acute rejection.